Multifaceted insights into the environmental adaptability of Arnebia guttata under drought stress - Liu, Qian; Liu, Haolin; Zhang, Min; Lv, Guoshuai; Zhao, Zeyuan; Chen, Xingyu; Wei, Xinxin; Zhang, Chunhong; Li, Minhui (Frontiers in Plant Science, 2024)
An arid climate restricts the quality development of medicinal plants. We collected climatic data and used ArcGIS software to analyse the climatic factors contributing to the distribution of Arnebia guttata resources in China. Based on textual research of traditional Chinese medicine and investigation of field resources, field samples were collected and tested, and seedlings were cultured in the laboratory to simulate drought treatment. The synthesis of shikonin and other active substances under the effect of drought and the stress resistance mechanism of A. guttata are discussed. A. guttata showed strong adaptability to drought environments; moderate drought stress promoted the accumulation of shikonin, and metabolic diversity was the basis of drought adaptation. Additionally, the eastern part of Inner Mongolia, the northwest and south of Xinjiang, and the north of Gansu were predicted to be the major areas suitable for A. guttata growth in the next 40 years. This study revealed the correlation between the formation of medicinal components and the climate of A. guttata and analysed its drought adaptation mechanism, thus providing valuable information for the sustainable development of resources and the improvement of medicinal value.